Caesarean delivery is associated with childhood general obesity but not abdominal obesity in Iranian elementary school children. (1st July 2014) - Salehi‐Abargouei, Amin; Shiranian, Afshin; Ehsani, Simin; Surkan, Pamela J.; Esmaillzadeh, Ahmad
Abstract Aim This study examined the association between Caesarean delivery and general and abdominal obesity among children. Methods In a cross‐sectional study, 635 children aged from 6 to 12 years of age (476 girls and 159 boys) were randomly selected from Isfahan elementary schools. Weight, height and waist circumference were measured. General obesity and abdominal obesity were defined based on World Health Organization growth charts and Iranian national cut‐off points, respectively. Parents were asked about delivery type and other factors potentially related to childhood obesity using a self‐administered questionnaire. The association between delivery type and obesity was examined using univariate and multivariate logistic regression models. Results The overall prevalence of general and central obesity was 17.6% and 17.1%, respectively, and Caesarean delivery was significantly associated with general obesity after controlling for potential confounders (OR: 2.46; 95% CI: 1.30–4.63, p = 0.005). We observed a significant association between Caesarean delivery and abdominal obesity in crude analyses (OR: 1.66; 1.02–2.69, p = 0.04), but this disappeared after adjusting for covariates (OR: 1.96; 0.82–4.69, p = 0.13). Conclusion Our results suggest that Caesarean delivery is adversely associated with general childhood obesity, but not abdominal obesity. This provides support for recommending vaginal births, unless contraindicated. Further research in large populations is required to confirm these findings.